Environmental literacy model in organic waste processing based on eco enzyme - Himma Aliyah Fiddien; Rully Khairul Anwar; Ute Lies Siti Khadijah (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. Community Reading Space or Taman bacaan masyarakat (TBM) can play a significant role in environmental literacy through literacy programs offered to residents. This study aims to examine the role and stages of environmental literacy in organic waste processing based on eco enzyme and to describe the program development strategy implemented.